1995
DOI: 10.2214/ajr.164.6.7754881
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of venoocclusive disease of the liver after bone marrow transplantation: value of duplex sonography.

Abstract: OBJECTIVE.The purpose of this study was to determine if duplex sonography of the hepatic vasculature can be used to detect venoocclusive disease in patients who have had bone marrow transplantation.SUBJECTS AND METHODS. Twenty-seven bone marrow transplant recipients were serially studied with hepatic duplex sonography before (n = 27) and biweekly after (n = 136) transplantation.Duplex waveforms were obtained from the hepatic artery and the portal and hepatic venous systems. Clinical records were reviewed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…The patient who is the subject of this report was noninvasively diagnosed as having VOD (8,10) although they were found to be not necessarily associated with VOD or were nonspecific for its diagnosis in several studies (7,11,12).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The patient who is the subject of this report was noninvasively diagnosed as having VOD (8,10) although they were found to be not necessarily associated with VOD or were nonspecific for its diagnosis in several studies (7,11,12).…”
Section: Discussionmentioning
confidence: 83%
“…Jones et There are many reports on the role of ultrasonography in the diagnosis of VOD (7)(8)(9)(10)(11)(12)(13) T a b l e 1 . Ul t r a s o n o g r a p h i c Me a s u r e me n t s a n d L a b o r a t o r …”
Section: Hepatic Veno-occlusive Disease (Vod) Is a Clinical Syndrome mentioning
confidence: 99%
“…Moreover, the inferior vena cava and major hepatic veins are usually patent. In one study, hepatic and portal vein color doppler findings in VOD patients were investigated, and in all the patients involved, normal hepatic venous flow was demonstrated [6]. A similar study on Budd-Chiari patients demonstrated that, despite the variability of portal venous flow findings, all patients had abnormalities of anatomy or of flow in one or more of the main hepatic veins [7].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, in a later study, these findings resulted in being of no value in the diagnosis of VOD. 20 The progression of color Doppler ultrasonographic vascular imaging techniques has made it possible to detect reversed portal flow with high sensitivity and reproducibility. In addition, hand-held equipment makes it easy and safe to handle the patient at the bedside in a bioclean room.…”
Section: Monitoring Of Hepatic Vod After Sct With Color Doppler Us M mentioning
confidence: 99%